SİNKRETİKLİYİN SƏCİYYƏVİ XÜSUSİYYƏTLƏRİ TÜRK DİLLƏRİNDƏ - Xudaverdiyeva Nərmin Siyavuş qızı (Scientific Research and Experimental Development, 2025)
Word-formation system of syncretic roots in the Azerbaijani and other Turkic languages is a complex hierarchical system in which oppositions of units of different structure and different degrees of complexity are detected. The specificity of this system is determined by its relations with lexicon and morphology of Turkic languages.